GAMBARAN PERSONAL HYGIENE ANAK USIA SEKOLAH DASAR YANG TINGGAL DI SEKITAR TPA NGRONGGO SALATIGA - Puspita, Dhanang; Messakh, Sanfia T.; Nuarika, Christintya (Universitas Kristen Satya Wacana, 2017)
Personal hygiene behavior is one effort to prevent the occurrence of various diseases due to microorganism from the waste. Children aged 6 - 11 years are still vulnerable awareness about personal hygiene. Factors of knowledge, environment, and family support become the determinants of personal hygiene practices by children. Children living in landfill have a greater risk of health disruption due to an environment that does not support personal hygiene. The purpose of this study was to look at the pattern of personal hygiene of primary school age children living in the TPA Ngronggo, Salatiga. This research is descriptive qualitative. Collecting data by interviewing respondents aged 6 - 11 years and living in landfill. The results obtained, most children do not fully understand and practice personal hygiene in their daily lives. Concluded if the children living in the landfill do not have the knowledge and practice of personal hygiene is good.